Apexification with apical plug in immature permanent maxillary incisor teeth: case report: Perawatan apeksifikasi dengan apical plug pada gigi permanen imatur insisivus rahang atas: laporan kasus - Lestari Hardianti Sugiaman; Nurhayaty Natsir (Makassar Dental Journal, 2022)
This article describes about the apexification of open apex with apical plug in immature permanent maxillary incisor teeth. A 12-year-old girl came to the Dental Hospital Hasanuddin University with a complaint of cavities in her upper front teeth. The teeth were filled one year ago, and it fell out about six months later. The right upper tooth had been swollen and sore a few days be-fore. There is a history of colliding at the age of 8 years. Radiographic examination showed a wide root canal on tooth 11 and an open apex with radiolucency in the apical area on teeth 11 and 21. So the diagnosis of these teeth was chronic apical abscess and asymptomatic apical periodontitis, respectively. After performing open access, the root canal was prepared using conventional cir-cumferential techniques, then dressing using calcium hydroxide was given for 2 weeks. Next, the apical plug procedure was per-formed using MTA. The patient showed no complaints of pain after treatment, and the size of the radiolucency image in the pe-riapical area of ​​the tooth was reduced. So, it is concluded that apexification treatment with apical plug is one of the effective treatment methods to overcome the problem of open apex in immature permanent teeth. Keywords: apexification, apical plug, mineral trioxide aggregate, open apex